Procedural Approach to Ultrasound-Guided Geniculate Nerve Blockade for Knee Pain in Patients with OA. Issue 6 (June 2022) - Henry, Stephen; Best, Thomas M.; Jose, Jean; Tiu, Timothy
Abstract: Ultrasound-guided genicular nerve block can provide excellent pain control for patients with knee OA. This procedure has the advantage of providing sensory blockade with concomitant sparing of motor compromise, which is observed when the femoral and its lateral femoral cutaneous branches are blocked. Once the geniculate nerve of interest is identified, the operator can use ultrasound guidance to surround nerve fascicles with an injectate mixture of anesthetic and corticosteroid, yielding decreased pain sensation at the joint capsule. Given the role of the geniculate nerve in providing sensory innervation to the joint capsule and knee ligaments, blockade of this nerve can serve as a useful tool for managing patients with acute knee pain secondary to OA.